2021
DOI: 10.1017/s1092852921000699
|View full text |Cite
|
Sign up to set email alerts
|

Mental pain as a global person-centered outcome measure

Abstract: Background Mental pain has been proposed as a global person-centered outcome measure. The aim of this cross-sectional study was to test an essential requisite of such a measure, namely that mental pain incorporates independent contributions from a range of discrete but disparate outcome measures. Methods Two hundred migraine patients were assessed concerning migraine disability, psychosomatic syndromes, mental pain, depression, anxiety, and psychosocial dimensions. General linear models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
5
0
6
Order By: Relevance
“…This is a transdiagnostic core characterization (50), with multiple expressions (51,52), providing an explanatory model for clinical phenomena (8). Relevant information can be obtained also assessing mental pain (53,54), which captures a feeling state characterized by emotional pain, emptiness, and internal perturbation (55), sometimes at the core of the suicidal process (56). Finally, a comprehensive assessment may also include evaluating specific positive features, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is a transdiagnostic core characterization (50), with multiple expressions (51,52), providing an explanatory model for clinical phenomena (8). Relevant information can be obtained also assessing mental pain (53,54), which captures a feeling state characterized by emotional pain, emptiness, and internal perturbation (55), sometimes at the core of the suicidal process (56). Finally, a comprehensive assessment may also include evaluating specific positive features, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the cross-sectional design of this study, we are unable to make any causal inferences about the observed variables. At the same time, clinical features such as anxiety, mental pain, and psychosomatic syndrome may also have an impact on the quality of life of patients with chronic illnesses but have not been systematically evaluated (53)(54)(55). Therefore, future longitudinal studies should address these questions and delve into the underlying mechanisms.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…In this sense, these complications can cause psychological distress that can lead to MDs if mental health care is not provided early on ( 1 , 12 ) . This condition impacts the daily lives of these people in individual, family, and community settings, and they can experience severe physical and emotional restrictions ( 3 , 13 ) . The complexity of the scenario requires early structured mental health care, with an emphasis on psychosocial needs ( 14 - 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Current health care is divided by specialty, and this reality makes care fragmented ( 1 ) . People with DM and MDs are not assisted according to the principle of comprehensiveness, as they are usually cared for by different teams that offer care for only one of the morbidities ( 3 ) . As far as the nursing team is concerned, nursing care stands out in health promotion, disease prevention, and health recovery and rehabilitation, which means that caring for patients with DM and MDs requires nursing professionals to take a broad view of the needs imposed by the disease.…”
Section: Introductionmentioning
confidence: 99%